Інформаційна технологія формування вигляду елементів технічних систем на основі дискретних даних щодо аналогів - Ugryumova, E. M.; Tronchuk, A. A.; Afanasjevska, V. E. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
Methodology and a computer decision support system for engineering system element habit generation are offered. Formal mathematical models of the system have been constructed using artificial neural networks. Control variables that are consistent with the desired quality criteria are determined on the basis of the evolutional method with regularization.